Application of meticulous nursing interventions for patients with stage 2 pressure injuries (精细化护理在2期压力性损伤患者中的应用效果观察) - XIE Lingzhi (谢玲芝) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of meticulous nursing interventions on wound healing in patients with stage 2 pressure injuries. Methods Totally 62 patients with stage 2 pressure injuries were divided into the observation group and control group, with 31 cases in each group. The control group received routine wound care, while the observation group was given meticulous nursing interventions. The nursing efficacy was measured. Results The averaged duration of wound healing in the observation group was shorter than that in the control group (P＜0. 01). Conclusion Application of meticulous nursing is potentially effective to shorten the wound healing time in patients with stage 2 pressure injuries. (目的 探讨精细化护理在2期压力性损伤患者中的应用效果。方法 62例2期压力性损伤的患者分为观察组和对照组, 各31例。对照组采用常规护理, 观察组采用精细化护理。评估2组护理效果。结果 观察组患者伤口平均愈合时间较对照组缩短, 差异有统计学意义(P＜0. 01)。结论 精细化护理干预能够缩短2期压力性损伤患者伤口愈合时间。)